KOLONIALISME DATA DI ERA DIGITAL: ANCAMAN HARMONISASI GLOBAL TERHADAP KEDAULATAN SIBER INDONESIA - Panggalih Husodo; Nurul Amin; Andri Rifandi; Fernandes Situngkir (Smart Education, 2026)
Abstract: Global digital transformation has created a new form of colonialism oriented toward the control of data, algorithms, and digital infrastructure through the domination of transnational technology corporations. The phenomenon of data colonialism develops when public data is extracted, monetized, and controlled by global digital platforms without proportional distribution of benefits to developing countries. This study aims to analyze the development of data colonialism through the harmonization of global digital regulations and its implications for Indonesia’s cyber sovereignty, while also formulating an ideal legal policy framework to strengthen national data sovereignty. This research employs a doctrinal (normative juridical) legal research method using statutory, conceptual, and philosophical approaches through the analysis of national regulations and the theories of data colonialism, cyber sovereignty, digital dependency, rule of law, and rule of code. The findings reveal that the harmonization of global digital regulations tends to represent the interests of developed countries and global technology corporations through the liberalization of cross-border data flows, which potentially weakens state control over strategic national data. The dominance of foreign digital platforms has caused Indonesia to experience structural dependency on foreign technology and digital infrastructure. The paradigm shift from rule of law to rule of code also demonstrates how algorithms and global platform systems are gradually taking over the state’s regulatory functions within digital spaces. Therefore, strengthening Indonesia’s cyber sovereignty requires a reformulation of digital legal policies through stronger data localization measures, the development of national data centers, the advancement of domestic technology, the reinforcement of cybersecurity systems, and the establishment of data governance oriented toward national interests and the protection of citizens’ digital rights. Keywords: Data Colonialism, Global Harmonization, Cyber Sovereignty, Data Protection. Abstrak: Transformasi digital global telah menciptakan bentuk kolonialisme baru yang berorientasi pada penguasaan data, algoritma, dan infrastruktur digital melalui dominasi korporasi teknologi transnasional. Fenomena data colonialism berkembang, ketika data masyarakat diekstraksi, dimonetisasi, dan dikendalikan oleh platform digital global tanpa distribusi manfaat yang proporsional bagi negara berkembang. Penelitian ini bertujuan untuk menganalisis perkembangan kolonialisme data melalui harmonisasi regulasi digital global serta implikasinya terhadap kedaulatan siber Indonesia, sekaligus merumuskan formulasi kebijakan hukum yang ideal dalam memperkuat kedaulatan data nasional. Penelitian ini menggunakan metode penelitian doktrinal (yuridis normative) dengan pendekatan peraturan perundang-undangan, konseptual, dan filosofis melalui analisis terhadap regulasi nasional, teori data colonialism, cyber sovereignty, digital dependency, rule of law dan rule of code. Hasil penelitian menunjukkan bahwa harmonisasi regulasi digital global cenderung merepresentasikan kepentingan negara maju dan korporasi teknologi global melalui liberalisasi arus data lintas negara yang berpotensi memperlemah kontrol negara terhadap data strategis nasional. Dominasi platform asing menyebabkan Indonesia mengalami ketergantungan struktural terhadap teknologi dan infrastruktur digital asing. Pergeseran paradigma dari rule of law menuju rule of code juga memperlihatkan posisi algoritma dan sistem platform global secara bertahap mengambil alih fungsi pengaturan negara dalam ruang digital. Oleh karena itu, penguatan kedaulatan siber Indonesia memerlukan reformulasi kebijakan hukum digital melalui penguatan data localization, pembangunan pusat data nasional, pengembangan teknologi domestik, penguatan keamanan siber, dan pembentukan tata kelola data yang berorientasi pada kepentingan nasional serta perlindungan hak digital masyarakat. Kata kunci: Kolonialisme Data, Harmonisasi Global, Kedaulatan Siber, Perlindungan Data.